2010
DOI: 10.1002/ppul.21366
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and gender on adherence to infection control guidelines and medical regimens in cystic fibrosis

Abstract: Study findings are suggestive of age-related differences in adherence behaviors across both IC and medical regimens and support the use of developmentally sensitive approaches to assessment and interventions addressing adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Whilst non-adherence to CF treatments is well-reported and linked to negative health outcomes [5][6][7][8][9] , adherence to IPC recommendations is less well-understood. Patient rates of avoiding contact with other people with CF are reported to be low (21%-27%), particularly in young adults 10,11 . Similarly, in a sample of UK adults (n=94), 35% reported mixing with others whilst in hospital, despite almost 64% having been informed of cross-infection risk 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Whilst non-adherence to CF treatments is well-reported and linked to negative health outcomes [5][6][7][8][9] , adherence to IPC recommendations is less well-understood. Patient rates of avoiding contact with other people with CF are reported to be low (21%-27%), particularly in young adults 10,11 . Similarly, in a sample of UK adults (n=94), 35% reported mixing with others whilst in hospital, despite almost 64% having been informed of cross-infection risk 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonadherence to inhaled therapies for cystic fibrosis remains a significant problem, especially during adolescence, and can influence lung function and health outcomes [22][23][24]. A survey of patients with CF and their parents found that the most common barriers to treatment adherence were lack of time, forgetfulness, and unwillingness to take treatment in public [25].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an explanation for this disparity coupled with a narrowing of the gender gap in recent times has sparked debate about whether such a gap ever existed, or whether the improvements observed can be explained by therapeutic advances or a greater compliance with therapy among female patients. Interestingly, Masterson et al studied adherence to infection control guidelines and medical therapy in a cohort of patients with CF, and found that although age-related differences exist, gender is not a significant factor associated with treatment adherence [18]. However, it is clear that female gender is a negative prognostic factor in CF, a finding that has been demonstrated in several countries, registries, and CF care centers.…”
Section: Gender Differences In Cfmentioning
confidence: 92%